2010
DOI: 10.1016/j.ahj.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking intensity and cessation on inflammatory markers in a large cohort of active smokers

Abstract: Background Cigarette smoking has been associated with increases in C-reactive protein (CRP) and leukocyte counts (WBC); however, the effects of smoking intensity and smoking cessation on inflammatory markers have not been evaluated prospectively in a large, modern cohort of current smokers. Methods WBC count and high-sensitivity CRP were measured in current smokers enrolled in a randomized, prospective clinical trial of five smoking cessation pharmacotherapies. Smoking intensity parameters included: cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 30 publications
6
57
0
1
Order By: Relevance
“…In our study, we did not consider exsmokers as a separate group due to the small numbers, so we could not assess the association between in flammatory marker levels and smoking cessation. However, other studies have shown smoking cessation reduces in flammatory markers but their levels do not fall to normal [28,29]. Therefore, our results reinforce the need to en courage smoking cessation as early as possible.…”
Section: Fbs = Fasting Blood Sugar; Tc = Total Cholesterol; Hdl-c = Hsupporting
confidence: 76%
“…In our study, we did not consider exsmokers as a separate group due to the small numbers, so we could not assess the association between in flammatory marker levels and smoking cessation. However, other studies have shown smoking cessation reduces in flammatory markers but their levels do not fall to normal [28,29]. Therefore, our results reinforce the need to en courage smoking cessation as early as possible.…”
Section: Fbs = Fasting Blood Sugar; Tc = Total Cholesterol; Hdl-c = Hsupporting
confidence: 76%
“…Articles are accumulating to report that smoking induces an increase in WBC counts, although this may not be due to inflammation of the respiratory tract [37]. Thus, Smith et al [38] observed that WBC counts were higher (7.4 9 10 3 cells/mm 3 ) among 839 male current smokers than among 2,421 male never smokers (6.2 9 10 3 cells/mm 3 ).…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have reported that smoking aligned with increased inflammatory markers [19,20]. Other authors have shown that the polymorphism -930A/G may modify the association between smoking and IMT values, particularly among healthy young adults [21].…”
Section: Discussionmentioning
confidence: 99%